2011
DOI: 10.1128/iai.05114-11
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae Yersiniabactin Promotes Respiratory Tract Infection through Evasion of Lipocalin 2

Abstract: Klebsiella pneumoniae is a pathogen of increasing concern because of multidrug resistance, especially due to K. pneumoniae carbapenemases (KPCs). K. pneumoniae must acquire iron to replicate, and it utilizes ironscavenging siderophores, such as enterobactin (Ent). The innate immune protein lipocalin 2 (Lcn2) is able to specifically bind Ent and disrupt iron acquisition. To determine whether K. pneumoniae must produce Lcn2-resistant siderophores to cause disease, we examined siderophore production by clinical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
277
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(298 citation statements)
references
References 36 publications
13
277
1
1
Order By: Relevance
“…Studies have shown that disrupting siderophore biosynthesis impacts central metabolism, which could affect the elaboration of other virulence factors and ultimately pathogenesis (48). Alternatively, elevated Ent levels have been detected in bacterial strains with mutations in the Aer and Ybt pathways, which could improve pathogenesis (49,50). Elevated Ent levels in ybtS-iucA may also explain the surprising increase in kidney colonization of cBSA-vaccinated mice infected with ybtS-iucA compared with iucA ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Studies have shown that disrupting siderophore biosynthesis impacts central metabolism, which could affect the elaboration of other virulence factors and ultimately pathogenesis (48). Alternatively, elevated Ent levels have been detected in bacterial strains with mutations in the Aer and Ybt pathways, which could improve pathogenesis (49,50). Elevated Ent levels in ybtS-iucA may also explain the surprising increase in kidney colonization of cBSA-vaccinated mice infected with ybtS-iucA compared with iucA ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The presence of pulmonary LCN2 per se could concurrently explain the dominance of LCN2-resistant bacteria such as S. pneumoniae or Haemophilus influenzae as causative pathogens of pneumonia. Klebsiella pneumoniae, another relevant lung pathogen that depends on enterobactin-like siderophores, evolved LCN2-resistant strains to evade LCN2-mediated growth inhibition (44).…”
Section: Discussionmentioning
confidence: 99%
“…While individual iron uptake mechanisms uniquely contribute to bacterial pathogenesis (13,40), it seems reasonable to assume that their similar function would allow for compensation. Of the four siderophores that UPEC isolates produce, three are so-called "stealth" siderophores (salmochelin, yersiniabactin, aerobactin) for their ability to avoid sequestration by lipocalin-2 (40,41). Isolating UPEC strains with all three stealth siderophore systems is uncommon, possibly due to their outer membrane receptors being the frequent target of bacteriophages and bacteriocins (42).…”
Section: Figmentioning
confidence: 99%
“…In addition, yersiniabactin is disproportionately associated with antibiotic-resistant strains, including Ͼ90% of strains of the E. coli sequence type 131 (ST131), an alarming pandemic multidrug-resistant (MDR) clonal group (48)(49)(50)(51), and Ͼ60% of respiratory carbapenemase-producing K. pneumoniae strains, compared to 10% of susceptible K. pneumoniae strains (41). Novel antimicrobial agents or vaccines that target yersiniabactin iron transport or other pathogen-associated nutrient acquisition systems may provide an effective strategy to combat the rising surge of antibiotic-resistant common infections.…”
Section: Figmentioning
confidence: 99%